An Extended CMOS ISFET Model Incorporating the Physical Design Geometry and the Effects on Performance and Offset Variation - Liu,Y; Georgiou,P; Prodromakis,T; Constandinou,TG; Toumazou,C (IEEE Transactions on Electron Devices, 2011)
This paper presents an extended model for theCMOS-based Ion-Sensitive-Field-Effect-Transistor (ISFET), incorporating design parameters associated with the physicalgeometry of the device. This can, for the first time, provide a good match between calculated and measured characteristics bytaking into account the effects of non-idealities such as threshold voltage variation and sensor noise. The model is evaluated through a number of devices with varying design parameters (chemical sensing area and MOSFET dimensions) fabricated ina commercially-available 0.35μm CMOS technology. Threshold voltage, subthreshold slope, chemical sensitivity, drift and noisewere measured and compared to the simulated results. The first and second order effects are analysed in detail and it is shown that the sensors’ performance was in agreement with the proposed model.